2017
DOI: 10.1111/pbi.12861
|View full text |Cite
|
Sign up to set email alerts
|

Long noncoding RNAs involve in resistance to Verticillium dahliae, a fungal disease in cotton

Abstract: SummaryLong noncoding RNAs (lncRNAs) have several known functions in plant development, but their possible roles in responding to plant disease remain largely unresolved. In this study, we described a comprehensive disease‐responding lncRNA profiles in defence against a cotton fungal disease Verticillium dahliae. We further revealed the conserved and specific characters of disease‐responding process between two cotton species. Conservatively for two cotton species, we found the expression dominance of induced … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
102
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 133 publications
(104 citation statements)
references
References 85 publications
2
102
0
Order By: Relevance
“…Our transcriptome and metabolic studies show that melatonin pre‐treatment upregulated the expression of phenylpropanoid pathway genes and increased lignin accumulation in cotton seedlings after V. dahliae inoculation (Figures and S3). Consistently, overexpression of GhLac1 and GhLac15 , genes related to phenylpropanoid pathway and lignin biosynthesis, was previously found to enhance V. dahliae resistance in cotton (Hu et al ., ; Zhang et al ., ,b). Transcriptional and histochemical analysis of resistant cotton ( G. barbadense cv.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our transcriptome and metabolic studies show that melatonin pre‐treatment upregulated the expression of phenylpropanoid pathway genes and increased lignin accumulation in cotton seedlings after V. dahliae inoculation (Figures and S3). Consistently, overexpression of GhLac1 and GhLac15 , genes related to phenylpropanoid pathway and lignin biosynthesis, was previously found to enhance V. dahliae resistance in cotton (Hu et al ., ; Zhang et al ., ,b). Transcriptional and histochemical analysis of resistant cotton ( G. barbadense cv.…”
Section: Discussionmentioning
confidence: 99%
“…The dormant microsclerotia of V. dahliae can survive in soil for many years (Klosterman et al ., ; Gao et al ., ; Zhao et al ., ). The typical symptoms of Verticillium wilt in cotton plants include leaf chlorosis and wilt, leaf defoliation, vascular tissue browning, and plant death (Xu et al ., ; Li et al ., 2016a; Zhang et al ., ,b). Its widespread and destructive effect has led to huge economic losses for the cotton industry in China (Xu et al ., ; Li et al ., ; Gong et al ., ).…”
Section: Introductionmentioning
confidence: 99%
“…Long non‐coding RNAs (lncRNAs) are transcripts of more than 200 nucleotides in length and have no apparent coding ability (Hao et al ., ; Wang and Chekanova, ). With the advent of next‐generation sequencing, thousands of lncRNAs have been identified in several plant species such as rice (Zhang et al ., ), Arabidopsis (Liu et al ., ; Di et al ., ), maize (Huanca‐Mamani et al ., ), tomato (Wang et al ., and c), wheat (Ma et al ., ), apple (An et al ., ), cotton (Zhang et al ., ) and others. Plant lncRNAs play important roles in seed development (Kiegle et al ., ), photomorphogenesis (Wang et al ., ), fruit development (Zhu et al ., ; Wang et al ., , ; Li et al ., ), microRNA (miRNA) silencing (Wang et al ., ), miRNA precursors (Chen et al ., ; Joshi et al ., ) and biotic and abiotic stress responses (Qin et al ., ; Wang et al ., ).…”
Section: Introductionmentioning
confidence: 83%
“…In Populus tomentosa , 3569 cis ‐regulated protein‐coding genes were predicted as potential target genes of lncRNAs to participate in biological regulation (Zhou et al ., ). After infection with TYLCV, Phytoplasma , Verticillium dahliae and F. oxysporum , lncRNAs in tomato, P. tomentosa , cotton and Musa acuminate affect the expression of their neighboring genes in response to these pathogens (Li et al ., ; Fan et al ., ; Zhang et al ., ; Wang et al ., ). Previous studies have shown that lncRNAs transcribed from the promoter region have a strong influence on the transcription of its downstream protein‐coding genes, and some lncRNAs regulate gene expression by forming a triple helix in the promoter of its downstream gene (Quan et al ., ).…”
Section: Discussionmentioning
confidence: 99%
“…The time-course RNA-seq analysis discovered 559 lincRNAs in response to Pectobacterium carotovorum subsp., and 17 of these lincRNAs were found to be highly co-expressive associated with 12 potato defense-related genes [48]. Similarly, 514 lncRNAs in resistant Gossypium barbadense were identified as species/lineage-specific (LS) lncRNAs involved in the resistance to Verticillium dahliae, a fungal disease in cotton [44]. Further functional analysis showed that GhlncNAT-ANX2-and GhlncNAT-RLP7-silenced seedlings displayed an enhanced resistance towards V. dahliae and Botrytis cinerea, possibly associated with the increased expression of lipoxygenase 1 (LOX1) and lipoxygenase 2 (LOX2) [44].…”
Section: Responding To Biotic Stress and Co-expression With Functionamentioning
confidence: 99%